What has Caenorhabditis elegans ever done for us?. Issue 11 (16th November 2021) - Greener, Mark
Abstract : The nematode Caenorhabditis elegans has many features that make it an excellent model for biological and medical research. This article discusses how the worm is facilitating drug discovery, reducing the number of mammals used in research and helping to cut research costs.